(untitled) (KULT_online, 2012)
As the title Cultural Ways of Worldmaking clearly implies, the essays of this collection take Nelson Goodman’s concept of ’worldmaking’ as a starting point. They harness the potential of Goodman’s constructivist approach for the study of literature and culture while also making use of concepts and methods of media studies, political science, and the science of history. One of the central questions is: how do media and narratives influence the process of worldmaking? Using examples as diverse as communication media, architectural projects, (fictional) biographies, "fictions of spirituality" and apocalyptic texts, the authors succeed in depicting the worldmaking potential of each.